Lindsey Salmon’s Mourning Process in Facing Sister’s Death in Alis Sebold’s The Lovely Bones - Nabilah Nisrina; Hadiyanto Hadiyanto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
This study analyzes the mourning process of Lindsey Salmon, one of the characters in Alice Sebold’s “The Lovely Bones”. This study aims to analyze the character of Lindsey Salmon, the conflicts experienced by Lindsey Salmon, and to identify Lindsey Salmon’s mourning process in coping with Susie Salmon’s death. The writer applies psychological approach to analyze Lindsey Salmon’s process of mourning to Susie Salmon’s death by using J. William Worden’s theory named “the Four Tasks of Mourning”. The result of the study shows Lindsey Salmon’s mourning process through four tasks: accepting the reality of the loss, processing the pain of the grief, adjusting to a world without the deceased, and finding an enduring connection with the deceased in the midst of embarking on a new life. From this study, it can be concluded that even though it takes her a long time, Lindsey Salmon is capable of overcoming her grief over Susie’s death and moving on with her life.Keywords: character; conflict; four tasks of mourning